IFPRI Malawi maize market report, November 2025 - International Food Policy Research Institute; Benson, Anderson (International Food Policy Research Institute, 2025)
Retail prices of maize decreased in nearly all monitored markets by 6 percent on average in November. Sustained imports at steady exchange rates helped stabilize prices at a time when they would normally rise as peak lean season approaches. Imports dominated maize trade at all border points except Mchinji, which recorded exports to Zambia.